(untitled) (Bulletin of criminological association of Ukraine, 2024)
In this article, it has been emphasized that the formation of a methodology for investigating the murders of hostages or kidnapped persons is one of the prerequisites for counteracting this type of crime and ensuring efficiency in the specified category of criminal proceedings. The factors that, in their aggregate, determine the prospects for the formation of a methodology for investigating the murders of hostages or kidnapped persons have been identified and characterized: qualitative and quantitative indicators of crime in general and in a separate sphere of social relations; the complexity of the mechanism for committing criminal offenses of a particular type (group); the lack of scientific works, information and reference and methodological literature that would form recommendations on criminal legal qualification, detection, documentation and pre-trial investigation; the low level of awareness of practitioners in the regularities of the mechanism for committing criminal offenses of a particular type (group), the features of organizing, planning and conducting theirinvestigation; the insufficient level of scientific development of the issues of investigating a particular type (group) of criminal offenses; the resonance of a criminal offense of a particular type; political, socio-economic and security changes in society that directly affect the criminogenic situation and the features of the implementation of criminal procedural activities, etc. It has been proven that the construction of the proposed separate forensic methodology is a predictive activity.